Strategi Manajemen Sumber Daya Manusia dalam Meningkatkan Kualitas Tenaga Kependidikan di Lembaga Pendidikan Islam - Ibnu Hajar Al Asqolani; Moh. Ali; Dewi Cahyani; Suklani Suklani; Hasan Al Banna (EduInovasi: Journal of Basic Educational Studies, 2026)
Education in the modern era demands that Islamic institutions be able to manage human resources professionally without abandoning the spiritual values that are their identity. This study aims to analyze human resource management strategies in improving the quality of educational staff at SMP Life Skill Nur 'Ala Nur, Cirebon City. This study uses a qualitative approach with descriptive methods, through data collection techniques in the form of interviews, observations, and documentation studies. Data analysis is carried out through a process of reduction, presentation, and drawing conclusions with validity tests using source and technique triangulation. The results show that the HR management strategy at SMP Life Skill Nur 'Ala Nur, Cirebon City includes needs planning, competency development, performance evaluation, and empowerment of educational staff based on Islamic values. This strategy has proven effective in improving the professionalism, loyalty, and spirituality of educational staff. The implications of this study indicate that the integration of Islamic values and modern management principles can be a model for sustainable human resource development for other Islamic educational institutions.